Reducing Emissions from Deforestation and Forest Degradation (REDD) Projects : Lessons for Future Policy Design and Implementation - Dulal, Hari Bansha; Shah, Kalim U.; Sapkota, Chandan (Taylor and Francis, 2013)
In response to the pressing global challenges of climate change, initiatives under the auspices of ‘reducing emissions from deforestation and forest degradation’ (REDD) have been implemented in over 30 developing and least-developed countries since 2005. The initiatives cover nearly every significant and vulnerable forest ecosystem worldwide. In this study we review six representative initiatives, two each from Africa, Asia and Latin America. Strength, weakness, opportunity and threat analysis is done to evaluate each initiative's policy framework, design, implementation and results thus far. The main policy and project implementation factors that appear to lead to effective and successful REDD project outcomes include having clearly formulated project design; governance, land tenure rights and capacity; equity and transparency; indigenous peoples' rights and knowledge; local–international coordination; and enhancing local and institutional capacities. Based on these findings, we provide recommendations for future REDD policy action and project implementation to make it work for the poor and achieve its intended goals.